Pemanfaatan Solar Cell pada Sistem Pertanian Hidroponik Cerdas di Samata Green House Group Indonesia, Kabupaten Gowa - Muslimin, Zaenab; Ahmad, Andani; Areni, Intan Sari; ., Dewiani; Akil, Yusri Syam; Salam, Ejah Umraeni; ., Wardi; Anshar, Muh; Mayasari, Fitriyanti; Achmad, Andini Dani (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Hydroponics is a planting technique using water-based nutrient solutions, not through soil media, like conventional farming. This hydroponic system solves the problems arising from soil-based farming that requires plowing and weeding and is susceptible to pests, climate, and the need for large land areas. However, to produce quality soil, the hydroponic system requires monitoring of nutrients, temperature, humidity, water content, pH, and light. Developing a smart hydroponic system or a system based on Artificial Intelligence of Things (IoT) can guarantee these parameters online or in real-time monitoring. The next problem is the need for a continuous and reliable supply of electrical energy so that the built AIoT-based hydroponic system can work optimally. Disruption of electrical continuity will affect the crop yields from this system. Therefore, the Community Service (PkM) activity from the Department of Electrical Engineering, Hasanuddin University, conducted socialization of the use of solar cells (solar panels) in the AIoT-based smart hydroponic system, which is a solution to the problem of the continuity of electricity supply at the Samata Green House (SGH) Group, as a partner of the activity, which still fully uses electricity from PLN. Based on the results of quantitative analysis of pre-test (before socialization) and post-test (after socialization) measurements by activity participants, an increase in the level of understanding of participants was obtained, which was initially 11-55% "quite understanding" to "understanding" of the components of the Solar Power Plant (PLTS) system, as well as how to operate and maintain PLTS, to 100% of participants "quite understanding" to "very understanding" regarding these parameters. This indicates that this activity has achieved the expected targets.